The Impact of the Constitutional Court Decision on Political Interests from a Shari'ah Perspective - Subro Molisi; Ade Fartini (Program Studi Hukum Tata Negara Fakultas Syariah UIN Maulana Malik Ibrahim Malang, 2025)
Constitutional Court (MK) decisions play an important role in the dynamics of political interests in Indonesia. As an institution that has the authority to review laws against the constitution, the Constitutional Court's decisions are often the basis for policy changes that have a significant impact on various parties. However, from a shari'ah perspective, these decisions are not only assessed in terms of legality, but also in terms of morality and the benefit of the people. This study aims to analyze the impact of the Constitutional Court's decision on political interests from a shariah perspective. Using qualitative normative research methods and literature studies, this research examines Islamic legal theories and principles of shari'ah that are relevant to interest politics. The results show that although the Constitutional Court's decisions are often oriented towards practical political interests, there is an ethical dimension in shariah that directs the importance of policies oriented towards the benefit of the people, justice and truth. In this case, the Constitutional Court's decisions must take into account the principles of shari'ah in order to realize policies that are in accordance with the Islamic goal of creating welfare and social justice.